Assessing Individual Muscle Characteristics to Enhance Frozen-Thawed Meat Quality - Im, Choeun; Song, Sumin; Cheng, Huilin; Park, Junyoung; Kim, Gap-Don (Food science of animal resources, 2024)
This study assessed previous research aimed at mitigating the adverse effects of freeze-thawing on meat quality. Specifically, it focuses on assessing the physicochemical alterations in meat resulting from freezing, freeze-thawing, or technologies to minimize these alterations. Recent studies have focused on conventional freeze-thaw technology applicable across various livestock species and muscle types. However, recent research has indicated the necessity for developing freeze-thaw technology considering the unique characteristics of individual muscles. In this review, we summarize previous studies that have compared alterations in the physicochemical properties of primary muscles owing to freezing or freeze-thawing. Despite the introduction of various technologies to significantly reduce the adverse effects on meat quality resulting from freeze-thawing, it is essential to consider the unique characteristics (proximate composition, pH, and muscle fiber characteristics) of individual muscles or cuts to develop enhanced the freeze-thaw processing technology.